Electrocatalysts: Ultrafine Defective RuO2 Electrocatayst Integrated on Carbon Cloth for Robust Water Oxidation in Acidic Media (Adv. Energy Mater. 35/2019). Issue 35 (19th September 2019) - Ge, Ruixiang; Li, Lei; Su, Jianwei; Lin, Yichao; Tian, Ziqi; Chen, Liang
Abstract : In article number 1901313, Ziqi Tian, Liang Chen and co‐workers report an ultra‐fine RuO2 catalyst, which is prepared via acid etching treatment of Zn‐doped RuO2 supported on carbon cloth. The leaching of Zn dopant leads to the formation of defects, resulting in more exposed active sites and improved intrinsic activity. The as‐prepared material exhibits a low overpotential of 179 mV for water oxidation in acidic media.